Formal Aspects in Security and Trust 6th International Workshop, FAST 2009, Eindhoven, The Netherlands, November 5-6, 2009, Revised Selected Papers - Degano, Pierpaolo; Guttman, Joshua D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-workshop proceedings of the 6th International Workshop on Formal Aspects in Security and Trust, FAST 2009, held under the auspices of IFIP WG 1.7 in Eindhoven, The Netherlands, in November 2009 as an event of the Formal Methods Week, FMweek 2009. The 18 revised papers presented together with an abstract of the invited lecture were carefully reviewed and selected from 50 submissions. The papers focus of formal aspects in security and trust policy models, security protocol design and analysis, formal models of trust and reputation, logics for security and trust, distributed trust management systems, trust-based reasoning, digital assets protection, data protection, privacy and id issues, information flow analysis, language-based security, security and trust aspects in ubiquitous computing, validation/analysis tools, Web service security/trust/privacy, grid security, security risk assessment, and case studies.
Invited Lecture -- Semantics and Enforcement of Expressive Information Flow Policies -- Session 1. Trust -- An Algebra for Trust Dilution and Trust Fusion -- HMM-Based Trust Model -- Deriving Trust from Experience -- Reflections on Trust: Trust Assurance by Dynamic Discovery of Static Properties -- Session 2. Workflow and Orchestration -- Model Checking of Security-Sensitive Business Processes -- Session 3. Secure Flow -- Analysing the Information Flow Properties of Object-Capability Patterns -- Applied Quantitative Information Flow and Statistical Databases -- Specification and Verification of Side Channel Declassification -- Secure Information Flow for Distributed Systems -- Session 4. Mobility and Deniability -- Probable Innocence in the Presence of Independent Knowledge -- A Calculus of Trustworthy Ad Hoc Networks -- Session 5. Protocols 1 -- Comparison of Cryptographic Verification Tools Dealing with Algebraic Properties -- Game-Based Verification of Multi-Party Contract Signing Protocols -- Attack, Solution and Verification for Shared Authorisation Data in TCG TPM -- Session 6. Protocols 2 -- Trusted Multiplexing of Cryptographic Protocols -- Specifying and Modelling Secure Channels in Strand Spaces -- Session 7. Protocols 3 -- Integrating Automated and Interactive Protocol Verification -- A User Interface for a Game-Based Protocol Verification Tool.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information storage and retrieval systems; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Systems and Data Security; Computers and Society; Management of Computing and Information Systems; Information Storage and Retrieval